2007
DOI: 10.1074/jbc.m609720200
|View full text |Cite
|
Sign up to set email alerts
|

Concentrative Export from the Endoplasmic Reticulum of the γ-Aminobutyric Acid Transporter 1 Requires Binding to SEC24D

Abstract: Re-uptake of ␥-aminobutyric acid (GABA) into presynaptic specializations is mediated by the GABA transporter 1 (GAT1), a member of the SLC6 gene family. Here, we show that a motif in the COOH terminus of GAT1 ( 566 RL 567 ), which is conserved in SLC6 family members, is a binding site for the COPII coat component Sec24D. We also identified residues in Sec24D ( 733 DD 734 ) that are required to support the interaction with GAT1 and two additional family members, i.e. the transporters for serotonin and dopamine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(140 citation statements)
references
References 33 publications
8
131
0
1
Order By: Relevance
“…These compounds effect recycling and internalization and thereby the density of SERT on the plasma membrane (21). The role of substrates in the trafficking of ␥-aminobutyric acid transporter (22,23), DAT (24), and the excitatory amino acid transporter 1 is to regulate the expression of the transporter on the cell mem-brane, i.e. glutamate increases the surface expression of excitatory amino acid transporter 1 (25).…”
mentioning
confidence: 99%
“…These compounds effect recycling and internalization and thereby the density of SERT on the plasma membrane (21). The role of substrates in the trafficking of ␥-aminobutyric acid transporter (22,23), DAT (24), and the excitatory amino acid transporter 1 is to regulate the expression of the transporter on the cell mem-brane, i.e. glutamate increases the surface expression of excitatory amino acid transporter 1 (25).…”
mentioning
confidence: 99%
“…It has been demonstrated that di-acidic motifs are involved in rapid concentration of cargo into the COPIIcoated vesicles and are able to directly bind to the COPII component Sec24 (1,2,6,13,55,56). We have demonstrated here that the function of the ExD motif in modulating AT2R transport to the cell surface is likely mediated through enhancing the recruitment of the cargo onto ER export sites or the COPII transport vesicles.…”
Section: Discussionmentioning
confidence: 65%
“…This interaction results in the concentration of cargoes in the ER exit sites and facilitates cargo recruitment onto the COPII vesicles (13).…”
mentioning
confidence: 99%
“…This is likely due to a slow ER exit for this mutant. Indeed, a role for K590 and L591 in sec24D binding and ER export has recently been reported for DAT, SERT and GAT (Farhan et al, 2007). It is interesting that the highly conserved K590 appears to play an important trafficking role, both at the level of ER exit and for regulated endocytosis.…”
Section: Discussionmentioning
confidence: 96%